Six artificial recharge pilot replicates to gain insight into water quality enhancement processes. (February 2020) - Valhondo, Cristina; Martínez-Landa, Lurdes; Carrera, Jesús; Díaz-Cruz, Silvia M.; Amalfitano, Stefano; Levantesi, Caterina
Abstract: The processes that control water quality improvement during artificial recharge (filtering, degradation, and adsorption) can be enhanced by adding a reactive barrier containing different types of sorption sites and promoting diverse redox states along the flow path, which increases the range of pollutants degraded. While this option looks attractive for renaturazing reclaimed water, three issues have to be analyzed prior to broad scale application: (1) a fair comparison between the system with and without reactive barrier; (2) the role of plants in prevention of clogging and addition of organic carbon; and (3) the removal of pathogens. Here, we describe a pilot installation built to address these issues within a waste water treatment plant that feeds on water reclaimed from the secondary outflow. The installation consists of six systems of recharge basin and aquifer with some variations in the design of the reactive barrier and the heterogeneity of the aquifer. We report preliminary results after one year of operation. We find that (1) the systems are efficient in obtaining a broad range of redox conditions (at least iron and manganese reducing), (2) contaminants of emerging concern are significantly removed (around 80% removal, but very sensitive to the compound), (3) pathogen indicators ( E. coli and Enterococci) drop by some 3–5 log units, and (4) the recharge systems maintained infiltration capacity after one year of operation (only the system without plants and the one without reactive barrier displayed some clogging). Overall, the reactive barrier enhances somewhat the performance of the system, but the gain is not dramatic, which suggests that barrier composition needs to be improved. Highlights: Six artificial recharge systems replicates were built to study the role of diverse parameters. Contaminants and pathogen indicators decrease efficiently along the systems. Reactive barriers favor quality water improvement. The specific role of plants should further be investigated.